Representations of Nation and Spanish Masculinity in Popular Romance Novels: The Alpha Male as "Other". Issue 2 (June 2019) - Pérez-Gil, María del Mar
The alpha hero embodies the hegemonic masculinity that has long dominated romance fiction. The portrayal of this male type is, however, problematized when he is an exotic foreigner, as his hyper-heterosexualized masculinity is often associated with the gender backwardness of his country. This article is concerned with popular romance novels set in Spain in the 1970s. It explores how British authors rely on gender and national clichés that construct an essentialized image of Spanish men. The primitive and instinctual masculinity attributed to them reveals these novels' complicity with the ideology of Britain's superiority.